Understanding suicidality in adolescents and young adults at clinical high risk for psychosis: a narrative review on risk factors and clinical insights - Pontillo, Maria; Di Vincenzo, Cristina; Di Luzio, Michelangelo; Demaria, Francesco; D’Aiello, Barbara; Bertoncini, Ilaria; Apicella, Massimo; Labonia, Milena; Maglio, Gino; Averna, Roberto; Vicari, Stefano (Frontiers in Psychiatry, 2025)
The prodromal stage of psychosis, referred to as the Clinical High Risk (CHR) phase, represents a critical period of heightened vulnerability to suicidality. Although suicidality is highly prevalent in CHR for psychosis (CHR-P) populations, research on this topic remains limited, often focusing more on the prevalence rates rather than the clinical implications. In this review, covering the past decade, we examined the prevalence and clinical significance of suicidality in adolescents and young adults at CHR-P. Our findings suggest that suicidality in CHR individuals arises from a complex interplay of depressive symptoms and both negative and positive symptomatology. Additionally, psychosocial stressors such as perceived stigma and discrimination further exacerbate suicide risk. Key risk factors include prior suicide attempts, impaired social functioning, psychiatric comorbidities, and stigma-related distress. Furthermore, anhedonia and suspiciousness emerged as independent predictors of suicidality. Suicidality rates vary by context, with higher prevalence in community-recruited CHR samples than in help-seeking individuals. This review highlights the need for a multidimensional suicide prevention approach, integrating early identification, comprehensive assessment, and targeted interventions. Future research should refine diagnostic tools, clarify the clinical trajectory from CHR to psychosis, and develop tailored intervention strategies to mitigate suicide risk in this population.